PENGETAHUAN IBU TENTANG KARIES GIGI PADA ANAK DI SEKOLAH DASAR HELVETIA MEDAN - Rostime Hermayerni Simanullang (Jurnal Online Keperawatan Indonesia, 2018)
Introduction: dental caries is a of infection diseases which destructive to structures teeth that causes hollow teeth. If not addressed, disease is causing pain, the calendar teeth, infection , various cases dangerous , and even death. Known that this case still highest in Asia. Purpose: to identify the correlation of mother knowledge level with the dental caries on child who are both in primary school. Method: the study is done by using the method descriptive a correlation in public primary schools no.066049 Bunga Raya, Helvetia Medan in December 2016. Samples to research consisting of 70 people mother with choose samples to cover by using tekhnik purposive sampling and analysis chi square. Result: the results of the study conducted with p value = 0.00 this showed that there was relations of mother knowledge level to dental caries on child. Conclusion: there was a correlation mother knowledge level to dental caries on child in public primary schools.